2014
DOI: 10.1186/1471-2164-15-170
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the Bifidobacterium brevetaxon

Abstract: BackgroundBifidobacteria are commonly found as part of the microbiota of the gastrointestinal tract (GIT) of a broad range of hosts, where their presence is positively correlated with the host’s health status. In this study, we assessed the genomes of thirteen representatives of Bifidobacterium breve, which is not only a frequently encountered component of the (adult and infant) human gut microbiota, but can also be isolated from human milk and vagina.ResultsIn silico analysis of genome sequences from thirteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
104
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 52 publications
(95 reference statements)
18
104
4
Order By: Relevance
“…2, we found that the putative sulfatase clusters are well conserved among the B. breve strains whose genomes were recently reported (71). Of currently available complete B. breve genomes, B. breve NCFB2258, B. breve 689B, B. breve 12L, and B. breve S27 encode clear homologues of both identified putative sulfatase gene clusters described above.…”
Section: Resultssupporting
confidence: 53%
“…2, we found that the putative sulfatase clusters are well conserved among the B. breve strains whose genomes were recently reported (71). Of currently available complete B. breve genomes, B. breve NCFB2258, B. breve 689B, B. breve 12L, and B. breve S27 encode clear homologues of both identified putative sulfatase gene clusters described above.…”
Section: Resultssupporting
confidence: 53%
“…All type strains belonging to the Bifidobacterium genus and several previously characterized strains belonging to species present on the qualified presumption of safety (QPS) list (11,13,19,(40)(41)(42)(43)(44) were used in this study (Tables 1 and 2). Cultures were grown under anaerobic conditions (2.99% H 2 , 17.01% CO 2 , and 80% N 2 ) in a chamber (Concept 400; Ruskin) on De Man-Rogosa-Sharpe (MRS) broth (Scharlau Chemie, Barcelona, Spain) supplemented with 0.05% (wt/vol) L-cysteine hydrochloride and were incubated at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The reconstruction of the pan-genome of this taxon revealed a wide genetic variability for genes previously characterized as being involved in the utilization of the carbohydrates ribose, sucrose, and raffinose, as well as the plant-derived polysaccharides starch, galactan, and cellodextrin (73).…”
Section: Figmentioning
confidence: 99%
“…Notably, the core genome of B. breve encompasses genes that are predicted to encode enzymes involved in the uptake and utilization of host-derived mono/oligosaccharides, in particular those derived from mucin and HMOs (73). Examples include gene clusters predicted to be involved in the metabolism of sialic acid, lacto-N-biose, fucose, and N-linked glycans.…”
Section: Figmentioning
confidence: 99%